Pengaruh Penggunaan Animasi Model TGT terhadap Hasil Belajar PKN Kelas IV SDN 61 Banda Aceh: The Effect of Using TGT Model Animation on Civics Learning Outcomes of Class IV SDN 61 Banda Aceh - Sakdiah Sakdiah; Musdiani Musdiani; Helminsyah Helminsyah (Information Technology and Science (ITScience), 2026)
This study evaluates the effectiveness of combining the Teams Games Tournament (TGT) learning model with animated audiovisual media in improving fourth-grade students' learning outcomes at SDN 61 Banda Aceh. The background of this study is low student interest and learning outcomes due to monotonous conventional methods, with the average initial score (pretest) at 65, which is still below the KKM standard of 75. Using a one-group pretest-posttest design with 27 students in the even semester of 2025/2026, data were analyzed using the Wilcoxon Signed-Rank test. The results showed a significant positive effect, with the average score increasing to 84.26. It was concluded that integrating animated media with the TGT model created an interactive, effective learning environment that improved students' cognitive understanding. Suggestions put forward include: for teachers, apply this strategy routinely in Civics and other subjects; for schools, provide multimedia facilities and teacher training; for future researchers, use a quasi-experimental design with a control group to strengthen validation.